Digital Transformation of the Village Correspondence Information System (SIPDES) in Supporting Good Village Governance: A Case Study of La’bo’ Village - Melki Garonga; Semuel Yacobus Padang (Diponegoro University, 2025)
This research focuses on the implementation of the web-based Village Correspondence Information System (SIPDES) in La’bo’ Village, North Toraja Regency, as a digital solution to address the limitations of conventional public service delivery. SIPDES was designed to transform the village correspondence process by enabling community members to submit letter requests and monitor their application status independently through mobile devices, thereby reducing the need for repeated physical visits to the village office. The system was developed using the structured Waterfall methodology and underwent comprehensive functional testing. Black Box Testing confirmed that all system features functioned as intended and complied with the specified requirements. Furthermore, the User Acceptance Test (UAT) demonstrated a high level of user approval, indicating that SIPDES is perceived as practical, user-friendly, and suitable for real-world implementation. The implementation of SIPDES has proven effective in improving administrative efficiency, enhancing service transparency, and simplifying access to village administrative services. These outcomes indicate that SIPDES contributes meaningfully to the improvement of public service quality and supports the broader objectives of digital governance and Good Village Governance at the village level.